2007
DOI: 10.1093/geront/47.5.578
|View full text |Cite
|
Sign up to set email alerts
|

Transportation and Aging: A Research Agenda for Advancing Safe Mobility

Abstract: Safe mobility is essential to continued engagement in civic, social, and community life, and to the human interactions necessary for health, well-being, and quality of life. When safe driving is no longer possible for older adults, safe and practicable alternative transportation must be available. Furthermore, older adults are individuals; they have specific needs, abilities, and resources. Not all older adults will have difficulty meeting their transportation needs and no single transportation solution will w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
169
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(188 citation statements)
references
References 42 publications
5
169
0
1
Order By: Relevance
“…However, less is known about the relationship between the driving cessation and the change on cognitive function in senior drivers [86]. For many seniors, driving cessation is a major life event and represents a significant loss of independence [87][88], causing negative social consequences that affect their psychological well-being [47,[89][90][91][92][93][94]. Individuals with social, mobility and spatial restrictions are more likely to develop cognitive degenerations such as MCI and Alzheimer's disease [95][96].…”
Section: Psychological and Cognitive Effects In Seniors Due To Car Drmentioning
confidence: 99%
“…However, less is known about the relationship between the driving cessation and the change on cognitive function in senior drivers [86]. For many seniors, driving cessation is a major life event and represents a significant loss of independence [87][88], causing negative social consequences that affect their psychological well-being [47,[89][90][91][92][93][94]. Individuals with social, mobility and spatial restrictions are more likely to develop cognitive degenerations such as MCI and Alzheimer's disease [95][96].…”
Section: Psychological and Cognitive Effects In Seniors Due To Car Drmentioning
confidence: 99%
“…The impairments associated with chronic health conditions can lead to impaired driving ability, with subsequent changes in driving patterns and/or increased risk of crash or injury Marshall, 2008). Loss of licensure for health reasons often has a negative effect on individuals' quality of life (Dickerson et al, 2007;Langford and Koppel, 2006;Oxley and Whelan, 2008;Pellerito, 2009), including low self-esteem, social isolation, depression and loss of independence; ultimately this contributes to greater need for family and community support (Anstey et al, 2005;Fonda et al, 2001;Marotteli et al, 2000;Ragland et al, 2004). As much as it is desirable to promote continued driving in older adults, the safety implications of the effects of health on driving require careful consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Driver licensing agencies, physicians, and other professionals also use screening tools, such as the Assessment of Driving-Related Skills (ADReS; Carr, 2010), which targets only the essential motor, visual, and cognitive functions for driving. Although screening tools are important for triggering the need for further evaluation, continued research is needed to determine their validity and reliability in real-world application (Dickerson et al, 2007).…”
mentioning
confidence: 99%
“…In fact, studies suggest that up to 25% of older adults continue to drive after a physician recommends the cessation of driving (Dobbs, Carr, & Morris, 2002). Moreover, because of their disability, people with dementia cannot be retrained or have modifications made to the car to correct for their deficits, as can be done with a physical disability (Dickerson et al, 2007). Adults with dementia are at an increased risk for unsafe driving and crashes (Fox, Bowden, Bashford, & Smith, 1997), and studies have shown that people with dementia often become lost when driving (Rowe, Feinglass, & Wiss, 2004;Silverstein, Flaherty, & Tobin, 2002).…”
mentioning
confidence: 99%